PENGARUH MODEL PEMBELAJARAN KOOPERATIF ROLE PLAYING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD - Sundari, Wulan; Muhammad Taheri Akbar; Susanti Faipri Selegi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is limited to the cooperative role playing learning model for fourth grade students in Indonesian language subject chapter 3, look around at SD Negeri 143 Palembang. Based on the problem formulation above, the aim of this research is as follows: